Film Hero With Messianic Traits - Plencner, Alexander (Communication Today, 2025)
The author deals with the messianic traits of a hero who is a protagonist of contemporary mainstream ﬁlm. Basic assumption of this paper is observation that despite the so-called “end of grand narratives” proclaimed by postmodern philosophers at the end of the last century, there are phenonema in culture clearly contradicting former predictions: renaissance of a novel, rising popularity of historical and fantastic stories and new heroes with complex character and genuine humanistic qualities. According to the author this proves the fact that human need for transpersonal values, moral patterns and stories carrying the message of meaningfulness of human des-tiny, is historically stable. The paper examines various representations of ﬁlm hero within the broader context of social meanings in cinema (social dimension of ﬁlm). The author describes psychoanalytic and anthropological concepts of hero as well as Jesus Christ as an archetype of Savior. Some of his special traits serve as a model for conceptualization of messianic hero and his basic characteristics. The text provides numerous examples of strong and weak heroes who alternately resurfaced the mainstream ﬁlm through the decades. The author believes that the former narcissistic action hero and insecure hero is being replaced with more authentic and vibrant hero: a character who is vulnerable and commited to sacriﬁce in favor of others at the same time.